Swissmod - A Model of the Swiss Electricity Market - Ingmar Schlecht; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2014)
We present a bottom-up electricity market model for Switzerland called Swissmod. It includes a detailed electricity network and hydropower representation. Swissmod captures the features and restrictions of run-of-river, yearly storage and pumped-storage power plants and combines this with a network model of the river and water stream system to take the interdependence of hydraulically coupled hydropower plants into account. In addition, the Swiss electricity network is represented using the DC load ow approach, allowing for spatial market evaluations. The model is developed as a deterministic optimization problem in GAMS. It provides an hourly resolution over a one-year horizon with an approximated representation of the surrounding European electricity markets. The aim of this paper is to outline the model and calibrate it to 2012 data.
Keywords: L94; Q4; 330; Switzerland; electricity markets; power ow; hydropower; nodal pricing